1990
DOI: 10.1159/000146870
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Diameter of the Lumbar Spinal Canal in Normal Adult Saudis

Abstract: Pathological changes in the diameters of the lumbar spinal canal may be associated with low back pain. The assessment of the size of the canal is therefore an important diagnostic procedure. Evidence suggests that there are ethnic differences in the dimensions of the canal. A radiogrammetric study was therefore undertaken to establish norms of the transverse diameter for the Saudi population. The results show that the transverse diameter of the canal in Saudis differs from that of other populations but the sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 8 publications
(16 reference statements)
3
19
0
1
Order By: Relevance
“…The interpedicular distance of the patients in our study was greater than that of Nigerians, Saudis and Koreans, but less than that of Spanish, Indian and healthy Turkish participants. 13,[16][17][18][19] The transverse diameter of the vertebral body in our population was similar to that observed in Nigerians, but was less than that seen in healthy Turkish people. 16,19 The cephalocaudal diameter of the pedicle is greatest at T12 and L1.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The interpedicular distance of the patients in our study was greater than that of Nigerians, Saudis and Koreans, but less than that of Spanish, Indian and healthy Turkish participants. 13,[16][17][18][19] The transverse diameter of the vertebral body in our population was similar to that observed in Nigerians, but was less than that seen in healthy Turkish people. 16,19 The cephalocaudal diameter of the pedicle is greatest at T12 and L1.…”
Section: Discussionsupporting
confidence: 75%
“…As a result, the morphometric diameters recorded for those 13,14 Age is also considered to be an important variable in describing the pedicular morphometry. 15 In our study, patients were from different age groups and, except for the transverse and sagittal diameters of the vertebral body, many of the parameters showed little change between these groups.…”
Section: Discussionmentioning
confidence: 99%
“…35 This relation is so steady that the ratio between the two was found to be constant (0.6) only at L1, L2 and L4. This ratio is equal to that estimated in Nigerians 7 and Saudis, 13 which was also 0.6 in both cases.…”
supporting
confidence: 53%
“…Other studies have been reported by Amonoo-Kuofi [9] on Nigerians, Postacchini et al [10] on Italians and Indians, Picraetal. [11] on Spanish subjects and Amonoo-Kuofi et al [12] on Saudis. Most importantly, the comparative studies by AmonooKuofi [9], Postacchini et al [ 10] and Piera et al [11] indi cated that there are morphometric differences between races.…”
Section: Introductionmentioning
confidence: 90%